Comparison of Microleakage in Class V Restorations Using Different Composite Resins and Techniques - Serdar Akarsu; Samet Atasoy (Mashhad University of Medical Sciences, 2021)
Introduction: The aim of this study was to compare microleakage in Class V restorations using different composite resins and application techniques. Methods: In this study, 60 cavities were prepared on the buccal and lingual surfaces of samples, 3 mm length (mesio-distal), 3 mm height (cervico-occlusal) and 2 mm depth. Samples were randomly divided into 6 groups. In Group 1, Grandio (Voco GmbH, Cuxhaven, Germany) was used with bulk technique, in Group 2 by horizontal incremental technique and in Group 3 by oblique incremental technique. SonicFill (Kerr, CA, USA) in Group 4, Filtek Bulk Fill Posterior Restorative (3M ESPE, st. Paul, USA) in Group 5, and Estelite Bulk Fill flow (Tokuyama, Japan) in Group 6  were used with bulk technique. After thermal cycle, samples were incubated in 0.2% methylene blue solution for 24 hours. They were sectioned longitudinally from the middle of cavity (buccolingually). Microleakage was evaluated by stereomicroscope (Nikon SMZ25, Tokyo, Japan). Kruskal-Wallis and Mann-Whitney U tests were used for statistical analysis. Results: Microleakage at the cervical margin was higher than the occlusal margin. There was no statistically significant difference between groups at the occlusal margin, but there was a significant difference between groups at the cervical margin (P₌0.02). In Groups using incremental techniques, less microleakage was observed. There was no statistically significant difference between groups using bulk technique. Conclusion: The use of incremental techniques in the restoration of cervical lesions may reduce microleakage.